THE SPIRIT WITHOUT MEASURE: Jesus as the Bearer and Giver of the Spirit in Luke-Acts - Oey Natanael Winanto; Paulus Eppang; Corry C. Prasetya (Sekolah Tinggi Teologi Widya Agape dan Perkumpulan Teolog Agama Kristen Indonesia, 2026)
The role of the Holy Spirit in the life of Jesus has often been overshadowed by the church’s focus on Jesus’ divine nature, resulting in an underdeveloped pneumatological dimension in Christology. This article addresses this gap by examining Luke-Acts as a unified narrative that portrays Jesus as both the unique bearer of the Spirit “without measure” (John 3:34, a Johannine echo that Luke implicitly affirms) and the giver of the Spirit to the church. Through a narrative-theological and redaction-critical method, the study analyzes key Lukan passages—the annunciation, the baptism, the Nazareth sermon, the resurrection, and the ascension—to demonstrate that Luke intentionally presents Jesus’ anointing as the model for the church’s reception of the Spirit. The findings reveal that Jesus’ possession of the Spirit is not merely functional or temporary but constitutive of his messianic identity as the second Adam and the true Israel. Furthermore, the same Spirit who empowers Jesus for prophetic mission is poured out at Pentecost, establishing the church as a community of Spirit-anointed witnesses. The article contributes to Lukan pneumatology and Spirit Christology by arguing that the “measure” of the Spirit in Jesus’ life is the norm for Christian initiation, and that the church’s missional identity is a direct extension of Jesus’ own anointing. This integrative model challenges both the reduction of Spirit reception to conversion and the separation of Jesus’ anointing from the church’s empowerment.